Effects of phonophoresis with gold nanoparticles on oxidative stress parameters in a traumatic muscle injury model. (23rd March 2016) - Silveira, Paulo Cesar Lock; Victor, Eduardo Ghisi; Notoya, Frederico de Souza; Scheffer, Debora da Luz; Silva, Luciano da; Cantú, Roberto Benavides; Martínez, Virginia Hidolina Collins; de Pinho, Ricardo Aurino; Paula, Marcos Marques da Silva
Abstract: The aim of this study was to evaluate the effects of therapeutic pulsed ultrasound with gold nanoparticles on oxidative stress parameters after traumatic muscle injury in Wistar rats. The animals were randomly divided into nine groups ( n  = 6 each): sham (uninjured muscle); muscle injury without treatment; muscle injury and treatment with dimethyl sulfoxide (15 mg/kg); muscle injury and treatment with gold nanoparticles (27 µg); muscle injury and treatment with dimethyl sulfoxide + gold nanoparticles (Plus); muscle injury and therapeutic pulsed ultrasound; muscle injury and therapeutic pulsed ultrasound + dimethyl sulfoxide; muscle injury and therapeutic pulsed ultrasound + gold nanoparticles; and muscle injury and therapeutic pulsed ultrasound + Plus. Gastrocnemius injury was induced by a single-impact blunt trauma. Therapeutic pulsed ultrasound (6-min application, frequency 1.0 MHz, intensity 0.8 W/cm 2 ) was used 2, 12, 24, and 48 h after trauma. Mitochondrial superoxide generation, lipid peroxidation, and protein carbonylation, and the activities of superoxide dismutase, glutathione peroxidase, and catalase were evaluated. The increase in the superoxide production and TBARS and carbonyl levels observed in the control group after muscle damage were reduced in animals exposed to therapeutic pulsed ultrasound plus nanoparticles. Similarly, antioxidants enzymes showed a decreased activity with the same treatment. Our work suggest that therapeutic pulsed ultrasound + dimethyl sulfoxide + gold nanoparticles has beneficial effects on the muscle healing process by inducing a decrease in oxidative stress parameters and most likely decreasing the deleterious effects of the inflammatory response.